Cuantificación de carbono orgánico en dos ecosistemas tropicales del bosque protector Casacay, provincia de El Oro - Palacios Alvarado, Jean Andres; Espinoza Montealegre, Jose Daniel (Machala : Universidad Técnica de Machala, 2024)
This study aims to quantify the storage of organic carbon in semi-deciduous and evergreen forest ecosystems of the Casacay Protected Forest, given its crucial role in climate change. To achieve this, diversity indices were developed, allometric equations were used for vegetation and soil samples were processed in the laboratory. The Shannon-Wiener diversity index was used to calculate diversity. In relation to the quantification of carbon in above ground biomass, data were obtained in field of diameter breast height, height, and wood density, the latter obtained through a database, for the application of previously selected allometric equations. For the quantification of soil organic carbon, composite samples were obtained at a depth of 0 to 30 cm and samples were obtained by cylinders with known volume to obtain the organic matter and bulk density variables respectively, through laboratory processing. Results by eosystem show species diversity values of 2,22 and 2,54 for semi-deciduous and evergreen forest ecosystems respectively. Mean biomass carbon values were 39,61 t/ha for semi-deciduous forest and 57,15 t/ha for evergreen forest. Finally, the calculated mean soil organic carbon values were 76,42 t/ha and 112,87 for semi-deciduous and evergreen forest ecosystems, respectively.
El presente estudio tiene como objetivo cuantificar el almacenamiento de carbono orgánico en los ecosistemas de bosque semideciduo y siempreverde del BPC, dado su papel crucial en la mitigación del cambio climático. Para lograrlo, se desarrollaron índices de diversidad, se utilizaron ecuaciones alométricas para la vegetación y se procesaron muestras de suelo en laboratorio. Para el cálculo de la diversidad se optó por la aplicación del índice de diversidad de Shannon-Wiener. En relación a la cuantificación de carbono en la biomasa, se obtuvieron datos dasómetricos en campo de diámetro altura pecho, altura, y densidad de madera, esta última obtenida mediante una base de datos, para la aplicación de las ecuaciones alométricas previamente seleccionadas. Para la cuantificación del COS, se obtuvieron muestras compuestas a una profundidad de 0 a 30 cm y muestras mediante cilindros con volumen conocido para la obtención de las variables de MO y DA respectivamente, mediante el procesamiento en laboratorio. Los resultados obtenidos por ecosistema, muestran valores de diversidad de especies de 2,22 y 2,54 para los ecosistemas de bosque semideciduo y siempreverde respectivamente. Los valores medios de carbono en la biomasa fueron 39,61 t/ha para el bosque semideciduo y 57,15 t/ha para el bosque siempreverde. Finalmente, los valores de medios de COS calculados fueron 76,42 t/ha y 112,87 para los ecosistemas de bosque semideciduo y siempreverde, respectivamente.
Keywords: BIOMASA; CAMBIO CLIMATICO; INDICE DE DIVERSIDAD; DENSIDAD DE MADERA